2021
DOI: 10.3390/su13073880
|View full text |Cite
|
Sign up to set email alerts
|

Alfalfa for a Sustainable Ovine Farming System: Proposed Research for a New Feeding Strategy Based on Alfalfa and Ecological Leftovers in Drought Conditions

Abstract: In the past 10 years, the average demand for meat and milk across the world has significantly increased, especially in developing countries. Therefore, to support the production of animal-derived food products, a huge quantity of feed resources is needed. This paper does not present original research, but rather provides a conceptual strategy to improve primary production in a sustainable way, in relation to forthcoming issues linked to climate change. Increases in meat and milk production could be achieved by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In this way, promising results have been obtained by inoculating drought-tolerant rhizobia in chickpea (Aulakh et al, 2020;Laranjeira et al, 2021), lentil (Sijilmassi et al, 2020), soybean (Igiehon et al, 2021;Omari et al, 2022), mungbean (Sapna & Sharma, 2020;Nawaz et al, 2021), pea (Prudent et al, 2019) and common bean (Figueiredo et al, 2008;Sijilmassi et al, 2020;Rodiño et al, 2021), leading to an improvement of legume drought tolerance and increasing yield under water stress. In addition, some osmotolerant rhizobial strains are also capable of surviving and nodulating efficiently under drought conditions in the soil (Fernandez-Aunioń et al, 2010;Mhadhbi et al, 2011;Viti et al, 2021), and its inoculation increases the drought tolerance in legumes (Kibido et al, 2019). Mhadhbi et al (2011) observed how the drought tolerance of common bean improved greatly after inoculating the plants with the osmotolerant strain Ensifer meliloti 4H41, isolated from common bean nodules from a Tunisian oasis (Mnasri et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, promising results have been obtained by inoculating drought-tolerant rhizobia in chickpea (Aulakh et al, 2020;Laranjeira et al, 2021), lentil (Sijilmassi et al, 2020), soybean (Igiehon et al, 2021;Omari et al, 2022), mungbean (Sapna & Sharma, 2020;Nawaz et al, 2021), pea (Prudent et al, 2019) and common bean (Figueiredo et al, 2008;Sijilmassi et al, 2020;Rodiño et al, 2021), leading to an improvement of legume drought tolerance and increasing yield under water stress. In addition, some osmotolerant rhizobial strains are also capable of surviving and nodulating efficiently under drought conditions in the soil (Fernandez-Aunioń et al, 2010;Mhadhbi et al, 2011;Viti et al, 2021), and its inoculation increases the drought tolerance in legumes (Kibido et al, 2019). Mhadhbi et al (2011) observed how the drought tolerance of common bean improved greatly after inoculating the plants with the osmotolerant strain Ensifer meliloti 4H41, isolated from common bean nodules from a Tunisian oasis (Mnasri et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The observed nodule reduction could be because water scarcity is one of the factors that most affect the rhizobia survival in their free-life phase (Hungria et al, 2000;Santillana Villanueva, 2021;Sindhu et al, 2020) and the nodulation process, affecting chemotaxis, initiation, formation and development of nodules (Omari et al, 2022;Sindhu et al, 2020;Viti et al 2021). In fact, under sufficiently prolonged or severe drought conditions the nodule formation can be completely inhibited (Gerosa-Ramos et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Olive leaves or solid mill wastes can be fruitfully used in animal feeding experimental studies [98][99][100][101] have shown the beneficial role of dietary administration of such byproducts due to their antioxidative properties for poultry industry. In particular, ref.…”
Section: Olive Leaves or Olive Cake Reused For Animal Feedmentioning
confidence: 99%